Determinan Pengambilan Keputusan Berkeadilan Konsultan Pajak - Sabaruddin Sabaruddin; Sulhendri Sulhendri; Septemberizal Septemberizal (Jurnal Akuntansi dan Governance, 2023)
Objectives. this studi aims to determine and analysis the effect of moral responsibility, selfish behavior, ethical action and sefl-control  on the fair decision of tax consultant.Design/method/approach. This research is a quantitative research that looks for relationships between variables. The research sample is a tax consultant in South Jakarta for reasons of geografhical affordability after the Covid 19 pandemic.  At the time of research  the number of tax consultant in South Jakarta could not be known, so the Lemeshow formula was used to determine the sample size. With this formula, it is known that the sampel is 67.24 which is rounded up to 67 people using the non probalility sampling method. Data obtained by distributing questionnaires. The analytical method used is multiple linear analysis with WarPLS version 7.0.Results/findings. Moral responsibility has a positif and significant effect on fair decision making. Selfish behavior has a significant negative effect, ethical behavior has a significant positive effect and self control has a non significant positif effect fair decision making.Theoretical contribution. The result of this research are expected to be one of the references in developing lesson plans as well as references in preparing a consultant’s code of ethics, specially in the field of taxation.Practical contribution. The result of this study become an alternative input for tax consultant in making decisions, especially in deciding the tax obligations of taxpayers (clients).Limitations. This research was conducted on tax consultant in South Jakarta, so the research results anly apply to the sample studied and do not represent tax consultant in general.